Communication Skills Profile of Elementary Teacher Education Students in STEM-based Natural Science Online Learning - Duhita Savira Wardani; Jajang Bayu Kelana; Zingiswa Mybert Monica Jojo (Profesi Pendidikan Dasar, 2021)
This study aimed to determine the communication skill profile of Elementary Teacher Education (ETE) students enrolled in natural science online learning-based STEM. Pre-experimental research with a one-shot case study design was used in this study. The study's sample consisted of 25 ETE students from a university in Cimahi. Observation and documentation were the techniques used in this study. The paired sample t-test was used to analyze the data. The descriptive analysis and hypothesis testing with the t-test were used to check the data validity. The findings of this study revealed that (1) there is an effect of STEM-based online science learning on ETE students' communication skills, (2) that most students are still in the Intermediate category for written communication and "does not meet the Standards" for oral communication skills, and (3) that students' communication skills in STEM-based science online learning still need to be optimized. The study's findings suggest that ETE lecturers in Indonesia should broaden their knowledge and perspectives in STEM-based learning and communication management. Second, ETE lecturers in Indonesia must take the assessment of communication skills more seriously. Last but not least, the government, with the help of researchers, must devise an excellent assessment system to overcome time constraints. The results of this study revealed that STEM-based online science learning is being implemented.